Dysfunctional Crohn's disease-associated NOD2 polymorphisms cannot be reliably predicted on the basis of RIPK2-binding or membrane association - Parkhouse, Rhiannon; Monie, Tom P. (Frontiers in Immunology, 2015)
Polymorphisms in NOD2 represent the single greatest genetic risk factor for the development of Crohn's disease. Three different non-synonomous NOD2 polymorphisms - R702W, G908R, L1007fsincC - account for roughly 80 % of all NOD2-associated cases of Crohn's disease and are reported to result in a loss of receptor function in response to muramyl dipeptide stimulation. Loss of NOD2 signalling can result from a failure to detect ligand; alterations in cellular localization; and changes in protein interactions, such as an inability to interact with downstream adaptor protein RIPK2. Using an overexpression system we analysed approximately 50 NOD2 polymorphisms reportedly connected to Crohn's disease to determine if they also displayed loss of function and if this could be related to alterations in protein localization and/or association with RIPK2. Just under half the polymorphisms displayed a significant reduction in signalling capacity following ligand stimulation, with nine of them showing near complete ablation. Only two polymorphisms, R38M and R138Q, lost the ability to interact with RIPK2. However, both these polymorphisms still associated with cellular membranes. In contrast, L248R, W355stop, L550V, N825K, L1007fsinC, L1007P and R1019stopstill bound RIPK2, but showed impaired membrane association and were unable to signal in response to muramyl dipeptide. This highlights the complex contributions of NOD2 polymorphisms to Crohn’s disease and reiterates the importance of both RIPK2-binding and membrane association in NOD2 signalling. Simply ascertaining whether or not NOD2 polymorphisms bind RIPK2 or associate with cellular membranes is not sufficient for determining their signalling competency.